KOMUNIKASI PEMASARAN SANGGAR BATIK KALPIKA DALAM MENJUAL KARYA SENI KAOS LUKIS BATIK YOGYAKARTA - Lukman Prayoga; Christina Rochayanti (Jurnal Paradigma, 2017)
Sanggar Batik Kalpika is one of business is producing batik craft has been since 1970. To sell batik artwork and shirts of painting that are getting eroded about there enthusiasts, there need to be the communications marketing strategy good to reach the desired target. The purpose of this research is to know the communication marketing strategy the applied Sanggar Batik Kalpika to sell shirts of painting artwork Yogyakarta. This research use the theory planning as thinking base of knew about the process or steps communication marketing strategy to sell shirts of painting artwork. The kind of research used is descriptive qualitative research. Tecnique data collection is by in-depth interview, observation, and study dokumentation. This research result indicates there are two marketing done in Sanggar Batik Kalpika that is directly and indirectly. Marketing communications directly to build a partnership with several parties, In the form of personal selling. As for marketing communications that indirectly covering publication, and conducted direct marketing. In the implementation of marketing comunikation, Sanggar Batik Kalpika already have marketing departments, but in manage not yet optimal. With the analysis of the advantages and disadvantages of marketing comunication conducted by research, is expected to provide contribution so that the product of shirts painting artwork Sanggar Batik Kalpika can continue increase sales.